2021
DOI: 10.3389/fpsyg.2021.648497
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity and Phylogenetic Continuity of Laughter and Smiles in Hominids

Abstract: Laughter and smiles are often, but not always, associated with positive affect. These expressions of humans help to promote social relationships as well as the development of cognitive and socio-emotional skills and they may have a positive impact on health and well-being, hereby covering a selection of fitness-relevant benefits. Both laughter and smiles of positive affect also occur early in human development and across cultures, suggesting deep roots in human biology. The present work provides an evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 113 publications
0
24
0
Order By: Relevance
“…Researchers argue that laughter is an evolutionary adaptation that predates human speech vocalizations (i.e., it is phylogenetically older), and likely has its origins in the emotional vocalizations and play utterances noted in humans and other non-human mammals (Bryant & Aktipis, 2014;Davila-Ross & Dezecache, 2021;Lavan et al, 2016). Laughter is often recognized as an indicator to others of mood and affiliation (Davila-Ross et al, 2009), and the rapid panting associated with the rough and tumble play of young hominids and juvenile primates may have evolved initially as a communicative tool for signaling harmless intent and encouraging continued play interactions (Bryant, 2020;Gervais & Wilson, 2005).…”
Section: Laughter As An Evolutionary Adaptation/dual Pathway Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers argue that laughter is an evolutionary adaptation that predates human speech vocalizations (i.e., it is phylogenetically older), and likely has its origins in the emotional vocalizations and play utterances noted in humans and other non-human mammals (Bryant & Aktipis, 2014;Davila-Ross & Dezecache, 2021;Lavan et al, 2016). Laughter is often recognized as an indicator to others of mood and affiliation (Davila-Ross et al, 2009), and the rapid panting associated with the rough and tumble play of young hominids and juvenile primates may have evolved initially as a communicative tool for signaling harmless intent and encouraging continued play interactions (Bryant, 2020;Gervais & Wilson, 2005).…”
Section: Laughter As An Evolutionary Adaptation/dual Pathway Hypothesismentioning
confidence: 99%
“…Laughter is often recognized as an indicator to others of mood and affiliation (Davila-Ross et al, 2009), and the rapid panting associated with the rough and tumble play of young hominids and juvenile primates may have evolved initially as a communicative tool for signaling harmless intent and encouraging continued play interactions (Bryant, 2020;Gervais & Wilson, 2005). This ability to volitionally modulate laughter to communicate social information (e.g., affiliation and intent) is not specific to humans and, therefore, likely dates back to a shared ancestor (Davila-Ross & Dezecache, 2021). At some point during the evolution of laughter, humans evolved a highly sophisticated speech production system, which further allowed them to use laughter in a variety of contexts in a sort of evolutionary "arms race" that not only favored those who were able to produce laughter intentionally but also favored those who could recognize it as volitional and decipher its meaning (Bryant & Aktipis, 2014).…”
Section: Laughter As An Evolutionary Adaptation/dual Pathway Hypothesismentioning
confidence: 99%
“…Davila-Ross and Dezecache (2021) recently challenged the Power Asymmetry Hypothesis. In contrast, they suggested that the human smile and laugh both evolved within the context of play and have a shared ancestry, referring to this as the ‘Complexity and Phylogenetic Continuity’ hypothesis.…”
Section: Darwin's Observations On Facial Displays Across Speciesmentioning
confidence: 99%
“…An explanation is also needed for the subtle but important differences in usage between smiles and laughs in humans. Davila-Ross and Dezecache (2021) provide evidence that the addition of bared teeth to a laugh or a play face appears not to substantially alter its meaning in chimpanzees, and that laughing is almost invariably accompanied by a smile in humans. However, the reverse does not appear to be true.…”
Section: Darwin's Observations On Facial Displays Across Speciesmentioning
confidence: 99%
“…Our actions are authentic and manifest as laughter when we fail through our playfulness. Laughing as a tool for healing is well established, and it is in our human nature (Davila-Ross and Dezecache 2021;Gonot-Schoupinsky, Garip, and Sheffield 2020;Yim 2016;Zijderveld 1983). Authentic laughter creates a unique energetic understanding and reaffirms our being; this is the primary life force for our clown nature (Amsden 2017).…”
mentioning
confidence: 99%